Lily Cai: capstone - Cai, Lily, artist (Colorado State University. Libraries, 2023)
The artist's statement: Since I was a child, I could not express myself like others so confidently. I felt no one would like me for who I am. I am an introvert and have some difficulties expressing my chaotic nature to others. Being a graphic designer allows me to express my true self and expression through digital media. It is a way to express my quirky and goofy side of me that I can't physically express. The materials I often use in my works are mostly digital applications such as Adobe Creative software such as Adobe Fresco, Illustrator, or InDesign for my illustrations. The process of creating my work is that I look over other artworks to try to understand what I want to create, then sketch out everything that I can think of. For most of my illustrations, I choose concepts that I want others to understand. Sometimes, I spend hours lost in my illustration working on characters that I feel people will love and understand.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design